2003
DOI: 10.2134/jeq2003.1735
|View full text |Cite
|
Sign up to set email alerts
|

Competitive Degradation between the Fumigants Chloropicrin and 1,3‐Dichloropropene in Unamended and Amended Soils

Abstract: Indianapolis, IN) have been developed as commercial formulations.The showed that workers might be exposed to high CP con- centrations (Maddy et al., 1983(Maddy et al., , 1984. Because of the

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
19
0

Year Published

2004
2004
2013
2013

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 27 publications
(41 reference statements)
4
19
0
Order By: Relevance
“…There was no clear trend of the application rate dependence of MITC or CP degradation. The range of microbial degradation of two fumigants in our experiments was comparable to the literature, where 50 to 80% of the total degradation of MITC in one agricultural soil (Gan et al, 1999; Dungan et al, 2003), 68 to 92% of the overall CP degradation in three agricultural soils (Gan et al, 2000), and 84% of CP degradation in one fresh agricultural soil (Zheng et al, 2003) were attributed to microbial degradation. Similar to the previous studies, our results indicated that biodegradation played a primary role in overall degradation of MITC and CP in forest nursery soils.…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…There was no clear trend of the application rate dependence of MITC or CP degradation. The range of microbial degradation of two fumigants in our experiments was comparable to the literature, where 50 to 80% of the total degradation of MITC in one agricultural soil (Gan et al, 1999; Dungan et al, 2003), 68 to 92% of the overall CP degradation in three agricultural soils (Gan et al, 2000), and 84% of CP degradation in one fresh agricultural soil (Zheng et al, 2003) were attributed to microbial degradation. Similar to the previous studies, our results indicated that biodegradation played a primary role in overall degradation of MITC and CP in forest nursery soils.…”
Section: Resultssupporting
confidence: 89%
“…The t 1/2 of CP at 560 kg ha −1 application rate in sterilized Byromville nursery soil was 7.6 d and abiotic CP degradation was significantly slower than at 140 and 280 kg ha −1 rates. A previous study indicated that CP was degraded predominantly by biodegradation in the soil, and t 1/2 of CP was 2.4 d in a sterilized Arlington sandy loam and increased 6.2 times in a fresh soil (Zheng et al, 2003).…”
Section: Resultsmentioning
confidence: 97%
“…It is suspected that further variability will occur when multiple fumigants are applied due to the nontarget effects of the coapplied fumigant on microbial communities. Zheng et al (2003) observed competitive degradation with 1,3‐D accelerating the degradation of CP. In the Florida trials, vapor concentrations of CP were higher in Site 3, which did not receive a coapplication of 1,3‐D (Fig.…”
Section: Discussionmentioning
confidence: 93%
“…The final breakdown products of chloropicrin are carbon dioxide, nitrate, and chloride. When applied with other fumigants, competitive degradation between CP and 1,3-D has been reported in amended and unamended soils (Desaeger et al, 2004;Zheng et al, 2003). Repeated fumigation generated accelerated CP degradation compared to the soil without fumigation history.…”
Section: → → →mentioning
confidence: 99%
“…MITC is effective against nematodes and a variety of weeds and fungal pathogens (Dungan and Yates, 2003). However, MITC fumigants should not be applied with 1,3-D or CP simultaneously because 1,3-D and CP transformation can be accelerated in the presence of MITC (Zheng et al, 2003). Therefore, MITC is often applied sequentially with CP or 1,3-D to better control weeds.…”
mentioning
confidence: 99%